A comprehensive survey of tools and techniques mitigating computer and mobile malware attacks. (June 2021) - Abijah Roseline, S.; Geetha, S.
Abstract: In this era of modernization, digital technology plays a major role in all facets of life. We are accustomed to using computers and smartphones to access information, create, express, communicate, and collaborate, contributing to our personal, social, and professional survival at a comfortable level. As the legitimate use of digital space has grown, so have the prospects for malice via swindlers, blackmailers, vandals, and other criminals, to benefit by creating and propagating malware. While the main motive of malware designers is to make surplus profit illegally, other trivial motives range from activism and pranks, espionage, cyber theft, as well as serious crimes like privacy breaches. Policing the expanding attack surface needs the development of competent anti-malware solutions with more generalization to detect even zero-day malware and resolve their incidences with minimal human intervention. Anti-malware solutions pick up effective strategies from static, dynamic, reverse engineering, and advanced machine learning techniques. An arms-race situation always exists between the malware authors and the anti-malware community. In this paper, we present a comprehensive investigation of computer-based and mobile-based malware, their countermeasures, and various detection methods. We also discuss the additional issues and the challenges of malware detection and finally highlight a few open research issues, directing the trends of malware/anti-malware development.